The Role of Hydrogen in the Energy Mix: A Scenario Analysis for Turkey Using OSeMOSYS - Hepnur Tetik; Gokhan Kirkil (Energies)
The urgent need to tackle climate change drives the research on new technologies to help the transition of energy systems. Hydrogen is under significant consideration by many countries as a means to reach zero-carbon goals. Turkey has also started to develop hydrogen projects. In this study, the role of hydrogen in Turkey’s energy system is assessed through energy modeling using the cost optimization analytical tool, Open Source Energy Modelling System (OSeMOSYS). The potential effects of hydrogen blending into the natural gas network in the Turkish energy system have been displayed by scenario development. The hydrogen is produced via electrolysis using renewable electricity. As a result, by using hydrogen, a significant reduction in carbon dioxide emissions was observed; however, the accumulated capital investment value increased. Furthermore, it was shown that hydrogen has the potential to reduce Turkey’s energy import dependency by decreasing natural gas demand.